"Incompleteness" and the Quest for Multiple Identities in South Africa. Issue 3 (December 2015) - Lategan, Bernard C.
The article explores the contours of multiple identities in contrast to singular identities in situations of social complexity and cultural diversity. Nyamnjoh's concepts of "incompleteness" and "frontier Africans" imply an alternative approach to identity formation. Although the formation of one's own, singular identity is a necessary stage in the development of each individual, it has specific limitations. This is especially true in situations of complexity and diversity and where the achievement of social cohesion is an important goal. With reference to existing theories of identity formation, an alternative framework is proposed that is more appropriate for the dynamic, open-ended nature of identity and better suited to encourage the enrichment of identity. The role of imagination, a strategy for crossing borders (with reference to Clingman's concept of a "grammar of identity"), the search for commonality, and the effect of historical memory are discussed. Enriched and multiple identities are not achieved by replacement or exchange, but by widening (existing) singular identities into a more inclusive and diverse understanding of the self.